2009
DOI: 10.1111/j.1537-2995.2009.02137.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of blood donors and donated blood in sub‐Saharan Francophone Africa

Abstract: The inclusion of these regions in future blood safety surveys and in the development of national blood transfusion programs is essential and will undoubtedly require the assistance of international organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 15 publications
9
82
1
4
Order By: Relevance
“…Pendant cette période, sept projets ont été réalisés à l'échelon national et publiés [3,[6][7][8][9][10][11] et cinq travaux multicentriques ont été conduits et publiés [12][13][14][15][16]. Seuls ces derniers sont rapportés ci-dessous.…”
Section: Travaux Réalisés Par Le Groupeunclassified
See 1 more Smart Citation
“…Pendant cette période, sept projets ont été réalisés à l'échelon national et publiés [3,[6][7][8][9][10][11] et cinq travaux multicentriques ont été conduits et publiés [12][13][14][15][16]. Seuls ces derniers sont rapportés ci-dessous.…”
Section: Travaux Réalisés Par Le Groupeunclassified
“…Les travaux réalisés sur ce thème ont été conduits en 2008 avec la participation de sept pays [12] et en 2011 avec celle de 15 pays [15]. Il est ainsi apparu que, dans les centres de transfusion d'Afrique sub-saharienne, le donneur de sang est habituellement jeune, avec un âge moyen de 26 ans (17-60 ans).…”
Section: Caractéristiques Des Donneurs De Sang Et Du Centre De Transfunclassified
“…The existence of risk factors for hepatitis B is associated with a higher prevalence of HBsAg [6,17]. However, our figure is in the proportions (2% -16%) reported in West Africa by Tagny et al [21]. The prevalence of HBsAg in our study was higher than that reported in a recent study in Madagascar [22], the Maghreb [23][24][25] or in other regions outside Africa [26,27], in connection with low endemicity of HBV in these regions.…”
Section: Prevalence Of Hbsagmentioning
confidence: 57%
“…Most studies in Africa reported a male dominance in blood donation programs (61% in Togo), (71.2% in Burkina Faso) and (90% in Ghana) [14][15][16]. In a recent survey in Central, Western, and Eastern Franco-phone African regions, all 7 countries surveyed reported less than 30% females in their donor population [17]. Reports from Anglophone East and Southern African countries have also shown a male dominance in their blood donation programs [18].…”
Section: Discussionmentioning
confidence: 99%